The decline in job-to-job flows - Henry R. Hyatt (IZA World of Labor, 2015)
As part of a more general process of employment reallocation from less to more productive employers, job-to-job flows tend to be beneficial for productivity and for workers. Thus, when this rate slows, it is important to understand why. In the US, for example, the job-to-job flow rate is now at an all-time low. While job-to-job flows are a means of boosting wages and productivity, a decline could indicate improvements for workers if it means that they are now better matched to their jobs. Furthermore, when job-to-job flows are lower, firms and workers incur fewer costs related to job transitions, such as job search and hiring costs.
Keywords: J62; J63; J64; E24; J23; 330; job-to-job; employer-to-employer; employment; hiring; firing; separations; layoffs; quits